Reversible thermo-pneumatic valves on centrifugal microfluidic platforms1. Issue 16 (21st August 2015) - Aeinehvand, Mohammad Mahdi; Ibrahim, Fatimah; Harun, Sulaiman Wadi; Kazemzadeh, Amin; Rothan, Hussin A.; Yusof, Rohana; Madou, Marc
<x xml:space="preserve">Abstract</x> Reversible thermo-pneumatic valves (RTPVs) manipulate thermal energy to reversibly block or open microchannels. The valves prevent the evaporation of reagents during thermocycling periods. The cartridge is used for sequential aliquoting to prepare multiple PCR reaction mixtures for the detection of the Dengue virus.